NONLINEAR GENERATION OF THE SECOND HARMONIC BY A LONG WAVE IN THE SHELF ZONE - Arsenyev S.S.; Rykunov L.N.; Sherkovnikov N.K. (My University, 1990)
Recent experimental studies of the nonlinear transformation of long waves in shallow waters indicate that the process involves the generation of higher harmonics that distort the shape of the long wave. To describe the generation of the second harmonic of a long wave, we consider the shallow-water equations.